Prevalence Of Toxoplasmosis In Hiv-I Sero-Positive Patients - ANEYMOL V. S.; WILLIAMSON M. (International Journal of Pharma and Bio Sciences, 2012)
Morbidity and mortality in HIV diseases is due to the occurrence of threatening opportunistic infections. Toxoplasma gondii is a cellular parasite (causative agent of Toxoplasmosis). Toxoplasma has been recognized as an important cause of morbidity and mortality among immunocompromised patients .The present study focuses on the incidence of Toxoplasmosis among HIV sero-positive. In the present study T.gondii co-infection was observed in 23% of HIV sero positive patients. 50% female and 57.7% of pediatric group were infected and were statistically significant (p< 0.01). Out of 23 pediatric patients studied for CD4:CD8 ratio, 14 patients were showing significant antibody titer with CD4:CD8 ratio in the range of 0.1- 0.7. The viral load of 14 patients was between 21,600 – 4, 97,429 eq/ml .Out of 14 T.gondii positive patients, 7 patients showed very weak viremia and remaining 7 showed moderate viremia